The change of environmental problem is very complex. The highest population growth caused supply of land and natural resources to be increased. If it does not control, it can influence natural resources stock and disturbs environmental balance system land use control is part of Bogor land use planning. The objectives of this research were (1) to analyze the dynamics of land use and population in the period of 1972-2005 in Bogor Municipality, (2) to develop dynamics model and analyze the relat - Yadi Suryadi; Surjono H. Sutjahjo; Bunasor Sanim; Ernan Rustiadi; Soekmana Soma (Forum Pasca Sarjana, 2008)
The change of environmental problem is very complex. The highest population growth caused supply of land and natural resources to be increased. If it does not control, it can influence natural resources stock and disturbs environmental balance system land use control is part of Bogor land use planning. The objectives of this research were (1) to analyze the dynamics of land use and population in the period of 1972-2005 in Bogor Municipality, (2) to develop dynamics model and analyze the relation between the instrument of land use control and the factors related to the sustaina tozbility of Bogor Municipality, and (3) to analyze stakeholders’ roles benefited to space control system in Bogor Municipality. The methods used for this research were (1) GIS analysis to observe the alteration influence landcover in period 1972-2005, (2) dynamic system analysis for landcover using in Bogor Municipality, and (3) AHP analysis to observe stakeholders’ role controlling use of landcover in Bogor Municipality. This research indicate that the dynamic of landcover such as forestry, mixed plantation, and open area (1972, 1983 and 1990) before to be extended were larger than after. For the landcover change such as resettlement, bush, water and wetland showed that were larger than before extended (2000 and 2005). The population dynamic analysis showed the optimum increasing on 1985-2020 (22,38%) but was not followed by good landcover use planning as indicated by forestry depletion from 25% to 2%, depletion of mixed plantation from 42% to 36%, resettlement need increased from 12% to 43%, and declining open area from 17% to 2%. These showed that Bogor developments were unsustainable. The dynamic analysis showed the correlation between the environmental component and land use control. Land use control to achieve Bogor sustainable development need many aspect such as land area, population number waste number, vehicle number, the length of roads and the role of stakeholder on land use control system in Bogor municipality though license mechanism and control. The government can influence land use control at level of controlling and level of licensing. For the government input as the authority that gives the permission of land using need to be consistent on the regulation they made. Key words: the dynamic, land use model, and controlling